Intelligent Decision Support Machines For Business Decisions - Gottinger, Hans W; Munich, STRATEC (Transactions on Engineering and Computing Sciences, 2018)
An intelligent decision support machine (IDSM) is a computer-based interactive tool of decision making for well-structured decision and planning situations that uses jointly decision-theoretic methods and machine learning techniques with access to structured data bases. An IDSM emerges from a model based system underlying a decision model (under uncertainty) imposing a normative (prescriptive ) structure of decision making. In the past years there has been substantial attention devoted to the use of artificial intelligence (AI) techniques, first most commonly rule-based expert systems, more recently methods of machine learning as tools for decision support. Based on those rules we design a machine learning algorithm guiding through principles of an IDSM.